2022
DOI: 10.3390/plants11030436
|View full text |Cite
|
Sign up to set email alerts
|

Extracts from Environmental Strains of Pseudomonas spp. Effectively Control Fungal Plant Diseases

Abstract: The use of synthetic chemical products in agriculture is causing severe damage to the environment and human health, but agrochemicals are still widely used to protect our crops. To counteract this trend, we have been looking for alternative strategies to control plant diseases without causing harm to the environment or damage to our health. However, these alternatives are still far from completely replacing chemical products. Microorganisms have been widely known as a biological tool to control plant diseases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Recent studies have shown that a variety of Pseudomonas sp. are widely used as biological control agents and have the advantage of colonizing plant roots and inhibiting a variety of plant diseases [55][56][57][58][59]. They prevent and control plant diseases by producing pathogen-resisting agents, such as antibacterial metabolites, proteases, lipases, and chitinases [60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that a variety of Pseudomonas sp. are widely used as biological control agents and have the advantage of colonizing plant roots and inhibiting a variety of plant diseases [55][56][57][58][59]. They prevent and control plant diseases by producing pathogen-resisting agents, such as antibacterial metabolites, proteases, lipases, and chitinases [60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…Another notable biocontrol agent is the bacterium Pseudomonas fluorescens . P. fluorescens has been extensively studied for its antagonistic activity against various postharvest fungal pathogens in fruits, including B. cinerea , P. expansum , and Monilinia spp . , It produces a range of secondary metabolites, such as phenazines and cyclic lipopeptides, which inhibit fungal growth and spore germination . For example, Kurniawan et al demonstrated that Pseudomonas effectively controlled gray mold caused by A. alternata and B. cinerea in postharvest strawberries, resulting in reduced disease severity and prolonged the fruit shelf life .…”
Section: Biological Controlmentioning
confidence: 99%
“…Among these, plant growth promoting rhizobacteria are of great interest ( Lugtenberg and Kamilova, 2009 ) since they induce not only stimulation of plant growth but can also protect against pathogens ( Beneduzi et al, 2012 ). Different studies described biological control agents (BCAs) that protect grapevine against gray mold disease ( Abbey et al, 2019 ; Bruisson et al, 2019 ; Esmaeel et al, 2019 , 2020 ; Amarouchi et al, 2021 ; Librizzi et al, 2022 ). Previous work on grapevine in vitro -plantlets demonstrated that Paraburkholderia phytofirmans strain PsJN can protect leaves against Botrytis by a combined effect: defense priming and direct antifungal effect ( Miotto-Vilanova et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%